Analisis Ketersediaan Air pada DAS Way Tembulih Untuk Kebutuhan Air Irigasi Berbasis Sistem Informasi Geografis di Kecamatan Ngaras Kabupaten Pesisir Barat - Riskia, Annissa Cindra; Ridwan, Ridwan; Amin, Muhammad; Asmara, Sandi (abe.fp.unila.ac.id, 2024)
The purpose of this research were to determine the amount of potential water resource for food crops (rice and secondary crops), determine the optimal planting area of food crops (rice and secondary crops) according to the potential of available water resource and determine the cropping pattern of food crops (rice and secondary crops) in accordance with potential available water resource. The research was carried out with the stages of land water balance analysis technique using the SWAT (Soil and Water Assessment and Tools) model, analysis of irrigation water needs, analysis of reliable discharge, and analysis of the adequacy of needs for potential available water resource. The result showed that the potential of river water resource in Ngaras District can meet the water needs of rice crops in the first and second planting seasons starting from the beginning of November to the end of June each covering an area of 108,38 ha and the third planting seasons for soybean crops starting from the beginning of July to the end of December covering an area of 43,352 ha. In order to achieve the target of available raw land of 216,7 ha, it is recommended to apply the irrigation arrangement pattern in groups and the construction of weir infrastructure. Keywords: Irrigation regulation patterns, Irrigation water needs, Water resource potential.